American Zinc Co. Mining Methods In East Tennessee District - M. J. Langley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1962)
Zinc ores were first discovered in Tennessee in 1856 at Jefferson City where a deposit became the Mossy Creek mine. From that time until 1913, small- scale attempts at prospecting and mining were made in various parts of the district. The actual systematic development of the zinc deposit dates from 1913 when the American Zinc Co. started operations at Mascot. Mining in the Mascot-Jefferson City area today is devoted exclusively to the zinc sulfide, sphalerite. Various grades of zinc mineralization have been found intermittently through a 600-ft vertical thickness. However, the commercial ore is confined to a total thickness of about 250 ft, from which it usually is mined irregularly from four or five separate levels known locally as "ore runs." In a few places vertical thicknesses up to 150 ft have been mined where commercial material extended from one run to another.